The Scope of the Principle of Autonomy in Genetic Testing - Stojkovic Zlatanovic, Sanja N (Glasnik Advokatske komore Vojvodine, 2020)
The paper aims to define the bioethical principle of the autonomy of the will in the conceptual-theoretical sense, and points to its legal significance. The basic legal derivatives of the principle of autonomy are identified, determinated as specialized patients rights, ie. the right to self-determination, the right to informed consent, and the right to privacy and confidentiality of health status information. This, in particular, in the context of conducting genetic testing, bearing in mind the specificities of genetic testing as a diagnostic measure. Genetic testing provides information on both, the current and future health status of an individual and their family members as well. Determining the scope of application of the principle of autonomy in the context of genetic testing has been defined as a basic research question that will be considered from contemporary theoretical points of view, but also through an analysis of the case law of the European Court of Human Rights.
Keywords: principle of autonomy, genetic testing, right to privacy, case law of the European Court of Human Rights